2020
DOI: 10.3389/fendo.2020.00360
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinical Outcomes in Newly Diagnosed Pediatric Type 1 Diabetes: Teamwork, Targets, Technology, and Tight Control—The 4T Study

Abstract: Many youth with type 1 diabetes (T1D) do not achieve hemoglobin A1c (HbA1c) targets. The mean HbA1c of youth in the USA is higher than much of the developed world. Mean HbA1c in other nations has been successfully modified following benchmarking and quality improvement methods. In this review, we describe the novel 4T approachteamwork, targets, technology, and tight control-to diabetes management in youth with new-onset T1D. In this program, the diabetes care team (physicians, nurse practitioners, certified di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 72 publications
3
45
1
Order By: Relevance
“…One caveat is that the benefits of CGM correlate with the frequency of and access to ongoing device use 3,4 . Early introduction to CGM in conjunction with health care provider/care team education and insulin‐dosing adjustments can allow for tighter glucose level ranges during the clinical remission phase 5 . It has also been shown that CGM initiation in the new onset period is in fact feasible and well accepted by youth and their families 6 .…”
Section: Introductionmentioning
confidence: 99%
“…One caveat is that the benefits of CGM correlate with the frequency of and access to ongoing device use 3,4 . Early introduction to CGM in conjunction with health care provider/care team education and insulin‐dosing adjustments can allow for tighter glucose level ranges during the clinical remission phase 5 . It has also been shown that CGM initiation in the new onset period is in fact feasible and well accepted by youth and their families 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since this analysis is part of an ongoing pilot study, additional participants were added weekly. 18…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced time and attention both during and outside of clinic are important in improving HbA1c outcomes, even in highly motivated patients. 7,10,74 Therefore, in addition to increased access to sophisticated insulin delivery and glucose sensor systems, patients and their families should also receive enhanced support necessary to overcome special barriers to management and assist with long-term acceptance and utilization. 75,76 Frequent contact with the family in their home could be accomplished with video conferencing apps.…”
Section: Can Technology Be Used To Overcome Racial Disparity In Hba1c Outcomes?mentioning
confidence: 99%